Dynamic force sensing of filamin revealed in single-molecule experiments - Rognoni, Lorenz (National Academy of Sciences, 2012)
Mechanical forces are important signals for cell response and development, but detailed molecular mechanisms of force sensing are largely unexplored. The cytoskeletal protein filamin is a key connecting element between the cytoskeleton and transmembrane complexes such as integrins or the von Willebrand receptor glycoprotein Ib. Here, we show using single-molecule mechanical measurements that the recently reported Ig domain pair 20–21 of human filamin A acts as an autoinhibited force-activatable mechanosensor. We developed a mechanical single-molecule competition assay that allows online observation of binding events of target peptides in solution to the strained domain pair. We find that filamin force sensing is a highly dynamic process occurring in rapid equilibrium that increases the affinity to the target peptides by up to a factor of 17 between 2 and 5 pN. The equilibrium mechanism we find here can offer a general scheme for cellular force sensing.